2019
DOI: 10.1101/579151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Balancing selection of the Intracellular Pathogen Response in natural Caenorhabditis elegans populations

Abstract: 23 0031317482998 24 Mark.Sterken@wur.nl 25 Our work provides evidence that balancing genetic selection shapes the transcriptional defence against pathogens 48 in C. elegans. The transcriptional and genetic data in this study demonstrate the functional diversity that can 49 develop within antiviral transcriptional responses in natural host populations. 50 Page 3 of 28 Background 51 The continuous battle between host and virus drives host genetic variation to arise in antiviral mechanisms such 52 as transcriptio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 88 publications
(247 reference statements)
2
18
0
Order By: Relevance
“…Four genomic regions were originally identified to affect C. elegans susceptibility to N. parisii , all of which overlap with hyper-divergent regions we identified. Subsequent studies showed that the pals genes mediate responses to N. parisii and the Orsay virus 31,[42][43][44][45] , of which 86.8% (33/38) of these genes are located in hyper-divergent regions. The hyper-divergent regions we present here also include other loci previously found to underlie natural resistance to starvation 59 and toxic bacterial metabolite 60 , and genetic incompatibilities in the species 29,61 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four genomic regions were originally identified to affect C. elegans susceptibility to N. parisii , all of which overlap with hyper-divergent regions we identified. Subsequent studies showed that the pals genes mediate responses to N. parisii and the Orsay virus 31,[42][43][44][45] , of which 86.8% (33/38) of these genes are located in hyper-divergent regions. The hyper-divergent regions we present here also include other loci previously found to underlie natural resistance to starvation 59 and toxic bacterial metabolite 60 , and genetic incompatibilities in the species 29,61 .…”
Section: Discussionmentioning
confidence: 99%
“…G-protein coupled receptors, GPCRs) are located in hyper-divergent regions. In addition to GPCRs, 48.2% (124/257) of genes that encode for C-type lectins, 53% (317/598) of the E3 ligase genes, and 86.8% (33/38) of the pals genes, which are involved in response to diverse pathogens 31,[42][43][44][45] , are found in hyper-divergent regions ( Supplementary Fig. 7, Supplementary Data 2).…”
Section: Maintenance Of Hyper-divergent Haplotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Next to this, we observed that infection tended to be more often established in N2 (76% success rate) than in CB4856 (61% success rate) (chi-square test, p = 0.093). Constant exposure to OrV for four days resulted in similar viral loads between N2 and CB4856 [15,26], thus suggesting that multiple rounds of viral replication are necessary to fully infect CB4856 populations. Together, these observations show that CB4856 develops a lower viral load and can suppress a beginning infection better than N2.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the natural variation in the RNAi response, genetic variation also determines the Intracellular Pathogen Response (IPR) against OrV infection. The Hawaiian strain CB4856 had higher (basal) expression of multiple IPR genes than N2, potentially resulting in higher resistance to OrV infection observed in CB4856 [26]. However, the genetic and transcriptional networks leading to this difference have not been uncovered.…”
Section: Introductionmentioning
confidence: 99%